Gambling on others’ health: risky pro-social decision-making in the era of COVID-19 - Loued-Khenissi, Leyla; Corradi-Dell’Acqua, Corrado (Frontiers in Psychology, 2024)
In the early days of the Covid19 pandemic, individuals were asked to perform costly actions to reduce harm to strangers, even while the general population, including authorities and experts, grappled with the uncertainty surrounding the novel virus. Many studies have examined health decision-making by experts, but the study of lay, non-expert, individual decision-making on a stranger's health has been left to the wayside, as ordinary citizens are usually not tasked with such decisions. We sought to capture a snapshot of this specific choice behavior by administering two surveys to the general population in the spring of 2020, when much of the global community was subject to Covid19-related restrictions, as well as uncertainty surrounding the virus. We presented study participants with fictitious diseases varying in severity that threatened oneself, a loved one or a stranger. Participants were asked to choose between treatment options that could either provide a sure, but mild improvement (sure option) or cure the affected person at a given probability of success (risky option). Respondents preferred gambles overall, but risk-seeking decreased progressively with higher expected severity of disease. This pattern was observed regardless of the recipient's indentity. Distinctions between targets emerged however when decisions were conditioned on a treatment's monetary cost, with participants preferring cheaper options for strangers. Overall, these findings provide a descriptive model of individual decision-making under risk for others; and inform on the limits of what can be asked of an individual in service to a stranger.